LOCUS OF CONTROL AND CIVIL SERVANT PERFORMANCE: THE MEDIATING ROLE OF WORK RESILIENCE - Sahrun Asis; Irsan Tricahyadinata; Dwi Martiyanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the role of work resilience as a mediating mechanism in the relationship between locus of control and civil servant performance in a highly regulated public organization in Indonesia. Drawing on the resource-based view and job demands-resources theory, this study positions locus of control as an upstream psychological resource that is converted into performance through adaptive capabilities. Data were collected from civil servants at the Samarinda Class I Harbormaster and Port Authority Office and analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that the locus of control significantly influences performance and strongly shapes work resilience, which subsequently improves performance. The significant indirect effect confirmed that resilience served as the primary transmission mechanism. These findings extend work control theory by emphasizing the importance of adaptive capabilities in explaining public sector performance and offer managerial implications based on strengthening work control and organizational resilience.